A structural-electrical property correlation in A-site double substituted lanthanum aluminate - Verma O.N.; Jha P.K.; Singh P. (My University, 2025)
The systematic study on structural properties of Ba-substituted La0.9Sr0.1Al0.9Mg0.1O3-δ and its correlation with conductivity was carried out. X-ray diffraction patterns indicated that the system formed a single phase composition up to 3% of Ba double substitution at the La-site. Energy dispersive X-ray spectroscopy and XPS results confirmed elemental compositions and revealed the maximum deficiency in oxygen for the 3% Ba-substituted sample. Dense grain formation is observed in SEM images, complementing higher density of these samples (>93%). Electrical conductivity was found to be in correlation with a new structural parameter of the critical triangle of (La/Sr/Ba)-Al/Mg-(La/Sr/Ba). The value of conductivity increased by an order of 2 in a substituted sample as compared to pure LaAlO3. The activation energy can be correlated with the area of the critical triangle of (La/Sr/Ba)-Al/Mg-(La/Sr/Ba). The migration path for ionic conduction of the oxygen ion was mapped out using the correlation of bulk conductivity with the A-A-B angle (β) and dc conductivity with the A-B-A angle (α). © 2017 Author(s).